2016
DOI: 10.4187/respcare.05012
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Leak Compensation in All-Age ICU Ventilators During Volume-Targeted Neonatal Ventilation: A Lung Model Study

Abstract: The PB980 and V500 were the only ventilators to acclimate to all leak scenarios and achieve targeted V. Further clinical investigation is needed to validate the use of leak compensation during neonatal volume-targeted ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 42 publications
(76 reference statements)
1
19
0
Order By: Relevance
“…Regarding the ventilators employed to deliver bilevel NIV, we have found some variability. Several bench studies have been published analyzing capabilities of different devices, and results differ according to the model (adult or neonatal) used . Unfortunately, there are no specific RCTs analyzing ventilators or ventilator‐interface effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the ventilators employed to deliver bilevel NIV, we have found some variability. Several bench studies have been published analyzing capabilities of different devices, and results differ according to the model (adult or neonatal) used . Unfortunately, there are no specific RCTs analyzing ventilators or ventilator‐interface effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to provide consistent and accurate V T and triggering has recently been evaluated across different volume-targeted modes and ventilator brands by using neonatal lung simulators with simulated ETT leaks. 4 However, there is a lack of data from human and animal studies to indicate whether volume-targeted mode performance of different ventilator brands has any effect on physiologic outcomes. We hypothesized that there would be no differences in ventilation parameters, gas exchange, triggering, or effort of breathing in surfactant-deficient, lung-injured, spontaneously breathing juvenile rabbits with and without an ETT leak among 3 different volume-targeted modes that monitor V T at different locations and regulate PIP based on inspiratory, expiratory, or leak adapted (compensated) V T .…”
Section: See the Related Editorial On Page 484mentioning
confidence: 99%
“…Recent studies have shown that, even if compensation algorithms can markedly reduce measurement errors, overall performance are not yet ideal [1627] and improvements are still needed, especially during variable leaks [28]. …”
Section: The Mechanical Ventilator: the Challenge Of Delivering Accurmentioning
confidence: 99%